2020
DOI: 10.1016/j.rpor.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy with or without oxaliplatin after short-course radiotherapy in high-risk rectal cancer: A subgroup analysis from a prospective study

Abstract: Aim: To evaluate the role of oxaliplatin in neoadjuvant chemotherapy delivered after short-course irradiation. Background: Using oxaliplatin in the above setting is uncertain. Patients and methods: A subgroup of 136 patients managed by short-course radiotherapy and 3 cycles of consolidation chemotherapy within the framework of a randomised study was included in this post-hoc analysis. Sixty-seven patients received FOLFOX4 (oxaliplatin group) while oxaliplatin was omitted in the second period of accrual in 69 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Preoperative RT reduces LR by approximately 50‑70% and postoperative RT by approximately 30‑40% in all locations of the rectum [ 34 , 35 ]. This effect may be enhanced by the use of concurrent chemotherapy [ 36 , 37 ], but are not observed, if adjuvant chemotherapy will be used after radiotherapy and radical resection [ 38 , 39 ]. Some studies reported a significant reduction in the risk of LR in anastomosis after anterior rectal resection after the use of preoperative 5 × 5 Gy sRT [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative RT reduces LR by approximately 50‑70% and postoperative RT by approximately 30‑40% in all locations of the rectum [ 34 , 35 ]. This effect may be enhanced by the use of concurrent chemotherapy [ 36 , 37 ], but are not observed, if adjuvant chemotherapy will be used after radiotherapy and radical resection [ 38 , 39 ]. Some studies reported a significant reduction in the risk of LR in anastomosis after anterior rectal resection after the use of preoperative 5 × 5 Gy sRT [ 35 ].…”
Section: Discussionmentioning
confidence: 99%